EFFECTS OF SERVICE QUALITY ON INPATIENT’S SATISFACTION AND LOYALTY: EMPIRICAL STUDY IN FATIMAH ISLAMIC HOSPITAL CILACAP - Zakki Kholid; Suci Paramithasari Syahlani; Satibi Satibi (Faculty of Pharmacy, Universitas Gadjah Mada)
The need for qualified hospital service has increased along with the improving economy and health ststus of the people. In recent years, the growth of private hospitals in Indonesia has showed significant development with the various regulations and legislation by the government. Therefore, in order to survive in the midst of competition, the Fatimah Islamic Hospital Cilacap should be able to provide a qualified service that’s oriented to achieve patient satisfaction that will lead to patient loyalty. This study was aimed to determine the effect of service quality on satisfaction and to know the effect of satisfaction with the loyalty of inpatients at the Fatimah Islamic Hospital Cilacap. The research was a crosssectional analytic with prospective data collection. The quantitative data were obtained by using a closed questionnaire. The questionnaire were given to 123 inpatients. Then the data were analyzed using multiple linear regression statistical method to investigate the effect of service quality dimension with satisfaction and simple linear regression methods to investigate the effect of satisfaction with the loyalty of inpatients at the hospital. The results showed that there was a positive effect between service quality and satisfaction of inpatients at the Islamic Fatimah Cilacap Hospital. The quality of service that give the most impact on patient satisfaction was tangible dimension with regression coefficient 0.244, while the smallest effect was the dimension of reliability with regression coefficient 0.185. In addition, this study also shows that there was a positive effect between patient satisfaction and loyalty of inpatients at the Fatimah Islamic Hospital Cilacap.Keywords: Service Quality, Patient Satisfaction, Patient Loyalty, Hospital